2010
DOI: 10.1007/s10915-010-9423-9
|View full text |Cite
|
Sign up to set email alerts
|

On the Linear Stability of the Fifth-Order WENO Discretization

Abstract: We study the linear stability of the fifth-order Weighted Essentially Non-Oscillatory spatial discretization (WENO5) combined with explicit time stepping applied to the one-dimensional advection equation. We show that it is not necessary for the stability domain of the time integrator to include a part of the imaginary axis. In particular, we show that the combination of WENO5 with either the forward Euler method or a two-stage, second-order Runge-Kutta method is linearly stable provided very small time step-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 21 publications
1
41
0
Order By: Relevance
“…The latter requirement is associated with a stable integration of the hyperbolic advection terms (see [24,36]). …”
mentioning
confidence: 99%
“…The latter requirement is associated with a stable integration of the hyperbolic advection terms (see [24,36]). …”
mentioning
confidence: 99%
“…In fact, these authors found out both in terms of linear stability theory and in simple numerical examples that forward Euler does not do well when complementing the WENO5 semidiscretization. Thus, the method that SSP methods "want to be like" is nothing to aspire to in the WENO context; see also [2,28].…”
Section: Ssp Methodsmentioning
confidence: 99%
“…But then WENO is unnecessarily working on the imperfection of the time discretization scheme. The net effect is the necessity when working with forward Euler of occasionally taking much smaller time steps than would otherwise be allowed; see also [28]. So, the SSP concept in its unmodified form may be irrelevant when a WENO semi-discretization is employed.…”
Section: Ssp Methodsmentioning
confidence: 99%
“…According to Wang and Spiteri [13], they are all linearly unstable in theory when coupled with the WENO5 scheme except TVD3. But the Courant numbers we use are small enough in terms of Motamed et al [20] to make the combination with WENO5 stable in practical applications. …”
Section: Definition 2 Assume Thatmentioning
confidence: 99%
“…The results are given for the smooth initial condition (19) in Tables A.14, A.15, A.16 and A.17 for the Euler forward, the TVD2, the TVD3, and the SSP RK(3,2) scheme, respectively. For the discontinuous initial condition (20), they can be found in Tables B.18, B.19, B.20 and B.21. In each row, the spatial resolution is fixed, whereas in the columns, the temporal resolution is constant.…”
Section: Errors Of Runge-kutta Schemesmentioning
confidence: 99%